Knowledge management initiative and solution: a case study in International Islamic University of Malaysia(IIUM) - Lubis, Muharman; Zamzami, Ikhlas F.; Fatani, Hanan A. A.; Ibrahim, Ismail M. M.; Ahmad Dahlan, Abdul Rahman (2011)
Universities are the important place for learning and sharing information internally or externally where the knowledge management (KM) implementation will give sustainable competitive advantage, achieving substantial savings, improve significant performance and establish the long-term existence among the others. The International Islamic University of Malaysia (IIUM) is a private publicly funded university in Malaysia while eight different governments from the Organization of the Islamic Conference (OIC) as its financial sponsor. So far, IIUM does not really have a system in managing the knowledge to inculcate a knowledge culture in development of education in Malaysia. This paper represents KM initiative and solution through investigating resource content and organization culture in IIUM in developing the appropriate KM framework that include set of plan and strategy based on ontology approach.